Chapter 1, 1000, 100.000. Quanti e quali attori nei costrutti personali indeterminati? - Fici, Francesca (Biblioteca di Studi Slavistici, 2016)
The aim of this article is to suggest a reflection on the indefinite-personal sentences of Russian. After a discussion of the properties of these sentences (1), we consider the grammatical and semantic characteristics of their components and especially of the null subject (2). In section (3) we consider which verbs occur more frequently in these sentences and in (4) the relationship among the different components of the indefinite-personal sentences. In (5) we conclude by briefly introducing the Italian sentences that most frequently correspond to Russian sentences of this type.